Barium isotopes in cold-water corals - Hemsing, Freya; Hsieh, Yu-Te; Bridgestock, Luke; Spooner, Peter T.; Robinson, Laura F.; Frank, Norbert; Henderson, Gideon (Earth and planetary science letters, 2018)
Recent studies have introduced stable Ba isotopes (δ138/134Ba) as a novel tracer for ocean processes. Ba isotopes could potentially provide insight into the oceanic Ba cycle, the ocean's biological pump, water-mass provenance in the deep ocean, changes in activity of hydrothermal vents, and land-sea interactions including tracing riverine inputs. Here, we show that aragonite skeletons of various colonial and solitary cold-water coral (CWC) taxa record the seawater (SW) Ba isotope composition. Thirty-six corals of eight different taxa from three oceanic regions were analysed and compared to δ138/134Ba measurements of co-located seawater samples. Sites were chosen to cover a wide range of temperature, salinity, Ba concentrations and Ba isotope compositions. Seawater samples at the three sites exhibit the well-established anti-correlation between Ba concentration and δ138/134Ba. Furthermore, our data set suggests that Ba/Ca values in CWCs are linearly correlated with dissolved [Ba] in ambient seawater, with an average partition coefficient of DCWC/SW = 1.8 ± 0.4 (2SD). The mean isotope fractionation of Ba between seawater and CWCs Δ138/134BaCWC-SW is −0.21 ± 0.08‰ (2SD), indicating that CWC aragonite preferentially incorporates the lighter isotopes. This fractionation likely does not depend on temperature or other environmental variables, suggesting that aragonite CWCs could be used to trace the Ba isotope composition in ambient seawater. Coupled [Ba] and δ138/134Ba analysis on fossil CWCs has the potential to provide new information about past changes in the local and global relationship between [Ba] and δ138/134Ba and hence about the operation of the past global oceanic Ba cycle in different climate regimes.
Available online 5 April 2018
Gesehen am 24.09.2019